Drivers of Loyalty: Integrating Service Quality, Marketing Mix, and Satisfaction - Nurdiansyah, Nurdiansyah; Amang, Baso; Alam, Roslina; Arifin, Arifin (International Review of Management and Marketing, 2026)
This study advances the understanding of student loyalty formation by re-examining the roles of service quality and the marketing mix within a developing-country higher education context—an area where empirical evidence remains limited and theoretically fragmented. Using survey data from 200 undergraduate students at Dipa Makassar University and analyzing the structural relationships through SEM, this research uncovers several novel insights. First, unlike dominant findings in Western and Asian higher education literature, service quality was found to exert no significant influence on either satisfaction or loyalty, revealing a contextual deviation that challenges the universality of traditional service quality models. Second, the marketing mix demonstrates a significant effect on satisfaction but not on loyalty, indicating that marketing-driven value stimuli require an intermediary psychological mechanism to translate into long-term commitment. Third, student satisfaction emerges as the primary and indispensable predictor of loyalty and partially mediates the effect of the marketing mix, while failing to mediate the service-quality–loyalty link. These results collectively offer a novel empirical configuration that reframes the pathway from institutional strategies to loyalty formation. Theoretically, the study extends relationship marketing theory by demonstrating that satisfaction functions as a conditional, rather than universal, mediator—its effectiveness shaped by local cultural and institutional dynamics. These insights contribute to refining higher education loyalty models in developing economies and offer new directions for context-sensitive theory building